Pengembangan Strategi Pemasaran Terpadu untuk Produk Unggulan Kelurahan Margaluyu Kota Serang - Iis Noviyanti; Riri Oktarini; Juwita Ramadani Fitria (Jurnal PKM Manajemen Bisnis, 2026)
Integrated marketing strategy is essential for strengthening the competitiveness of local superior products in Margaluyu Urban Village, Serang City, especially for home-based enterprises facing limited market access and digital marketing capabilities. This PKM program aims to develop an integrated marketing strategy to enhance product competitiveness, expand market reach, and improve entrepreneurial capacity among local producers. The PKM activity was conducted at the Margaluyu Village Office on 17 May 2026, involving six lecturers from Universitas Pamulang and 21 home-based business participants, through presentation sessions, practical training, discussions, and question and answer, following preparation, implementation, and reporting stages. The results of the activity showed increased understanding of integrated marketing strategies, improved branding and digital marketing skills, and greater awareness among participants in developing more competitive and sustainable business practices. In addition, the program encourages sustainable collaboration between lecturers and participants through follow-up mentoring and continuous assistance, enabling home-based enterprises to strengthen product innovation, marketing networks, and long-term competitiveness in both local and regional markets and improving income stability and community welfare in Margaluyu through strengthened entrepreneurship ecosystems and technology-based marketing adoption in sustainable local economic development context of Serang City area.